Experience of transcultural nursing for migrant workers in covid-19 field hospitals: a qualitative study in Samut Sakhon Province, Thailand - Arayathanitkul, Bussarin; Bandansin, Jutarat; Lamtrakul, Su-ari; Kwiensungnoen, Pacharaphorn; Eaksamai , Suwaluck (Jurnal Ners, 2024)
Introduction: This study aimed to explore Thai nurses’ experiences of caring for migrant workers with COVID-19 in a field hospital. Methods: This is a qualitative study. An in-depth interview was used to collect data from nine nurses between May and September 2022. The data were transcribed verbatim and content analysis was performed to analyze the data. Interviews with interpreters and co-workers of participants in the field hospital were used to examine data triangulation. Results: Three themes described the transcultural nursing experiences of nurses caring for COVID-19 migrant patients: 1) the role of nurses in a field hospital caring for migrant patients with COVID-19, 2) care delivery through the nursing process, and 3) cultural competence and transcultural nursing approach under mask and personal protective equipment for migrants with COVID-19 in the field hospital. Conclusions: Nurses' experiences highlighted the crucial role of managing patient care resources, coordinating with other healthcare professionals, and providing direct patient care in various situations in a field hospital. Despite mental and cultural care challenges, nurses still embrace transcultural nursing for migrant patients, addressing cross-cultural communication and basic needs and respecting beliefs related to religion to provide optimal care. Keywords: transcultural nursing, covid-19 field hospital, migrant workers, migrant patients